Exploring patient-borne costs and wait times for obstructive sleep apnea (OSA) care among rural and urban adults. Issue 1 (2nd January 2023) - Fatima, Duaa; Tsai, Willis H.; Corrigan, Jennifer; Ogah, Imhokhai; Ip-Buting, Ada; Sharpe, Heather; Laratta, Cheryl R.; Peller, Peter; Pendharkar, Sachin R.
Abstract: RATIONALE: Geography is an increasingly recognized barrier to the diagnosis and treatment of chronic diseases, yet no prior studies have investigated its influence on the patient-borne burden of obstructive sleep apnea (OSA) care. OBJECTIVE: We aimed to determine if wait times and costs of OSA care differ between rural and urban adults. METHODS: We conducted a secondary analysis of data from a prospective cohort study comparing OSA treatment outcomes among urban and rural adults. Participants were recruited at the time of continuous positive airway pressure (CPAP) initiation for uncomplicated OSA. Residential postal codes were translated into geographic census areas to classify participants as urban (community size > 100, 000) or rural. Participants were administered a questionnaire exploring wait times and costs of OSA care at baseline and three months. RESULTS: We enrolled 242 participants (100 rural). Twenty-six percent of respondents waited at least six months to seek medical attention for possible OSA, with no difference between groups. Wait times for diagnosis and treatment were three months or less for 91 and 93% of respondents, respectively. However, rural respondents experienced longer delays from first assessment to diagnosis and from diagnosis to treatment. Fewer individuals with rural residence were supported by government funding for diagnostic testing or CPAP. Rural participants more commonly reported additional appointment-related costs and greater total costs of care. CONCLUSION: Rural patients experience longer wait times and a greater financial burden for OSA care. The findings of this study will inform the development of novel models of OSA care sensitive to the needs of unique populations.